Object-Oriented Petri Nets Virtual Organization Structure (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Managing a mega organization has become an extremely complex task, especially if the organization is virtual. The operating structure of such a multi-faceted organization is very difficult to construct, and traditional organization structure models seem to fall short in coping with the demands imposed by such huge and complex entities. The object-oriented (organic) structure has many attributes that are suitable for solving the complexity of such organization structure and seems successful in catering for the needs of big organizations. However, the organic structure is by nature a static model that does not allow for predicting dynamic operation problems before they occur. The goal of this paper is thereforto design a generic model, using a Petri net-based framework, to simulate the workflow of virtual organizations that follow the organic structure in essential tasks like scheduling, monitoring and supervising.This model is useful in predicting problems before they occur and is therefore quite a useful tool for resource allocation, business planning and overall monitoring. Because of its capability in predicting problems like deadlock, priority inversion and starvation, a Petri net may become an essential tool for organization management.